AAV-mediated local delivery of interferon-β for the treatment of retinoblastoma in preclinical models - Shih, Chie-Schin (2009)
Interferon-β (IFN-β has been found to have anti-tumor properties against a variety of malignancies through different mechanisms. However, clinical trials involving systemic administration of IFN-β have been hampered by secondary toxicity and the short half-life of IFN-β in the circulation. In order to circumvent these limitations we have developed an adeno-associated viral (AAV) vector gene therapy approach to deliver IFN-β to tumors. In this study, we tested the efficacy of AAV mediated local delivery of IFN-β for the treatment of retinoblastoma in preclinical models. Retinoblastoma is an ideal candidate for gene-therapy based anti-cancer treatment because target cell transduction and, therefore, IFN-β delivery can be contained within the ocular environment, thereby minimizing systemic toxicity. We report here that retinoblastoma cell lines exhibit pleiotropic responses to IFN-β consistent with previous studies on a variety of tumor cell lines. Intravitreal injection of AAV-IFN-β resulted in efficient retinal infection and sustained IFN-β production in the eye with minimal systemic exposure. Vector spread outside of the eye was not detected. Using our orthotopic xenograft model of retinoblastoma we found that intravitreal injection of AAV-IFN-β had a potent anti-tumor effect in vivo. These data suggest that AAV mediated delivery of IFN-β may provide a complementary approach to systemic chemotherapy which is the standard of care for retinoblastoma around the world.